Association of focus score and extraglandular involvement in Sjögren’s syndrome: A study on antinuclear antibodies and minor salivary gland pathology - Mustafa Çağrı Ergün; Okancan Yılmaz; Hakan Bilgen; Pembe Oltulu; Fahriye Kılınç; Recep Tunç (Archives of Rheumatology, 2024)
Objectives: This study aimed to investigate the relationship between patients with and without extraglandular involvement in Sjögren’s syndrome (SS) by analyzing ANA (antinuclear antibody) and ENA (extractable nuclear antigen) results and minor salivary gland pathology findings. Patients and methods: A total of 265 (245 females; 20 males; mean age: 50.4±12.4; range, 19 to 79 years) patients diagnosed with SS were included in the retrospective cohort study between March 1, 2011, and December 1, 2021. Detailed documentation was performed, capturing demographic characteristics, clinical information, laboratory findings, medication usage, and manifestations of the syndrome. The patients were divided into two groups, with (78 females; 8 males; mean age: 52.7±11.5; range, 22 to 78 years or without (167 females; 12 males; mean age: 49.3±12.8; range, 19 to 79 years extraglandular involvement. Results: The mean follow-up duration was 63.1±31.9 months. Extraganular involvement, including joint involvement, lung involvement, central nervous system involvement, hematological involvement, hepatitis, and lymphoma, was observed in 32.5% of the patients. Patients with extraglandular involvement required multiple medications, while those with only glandular involvement predominantly used hydroxychloroquine. The mean duration from SS diagnosis to extraglandular involvement was 15.2±27.8 months. The comparison between patients with and without extraglandular involvement revealed a significant association between higher focus scores (FS) and extraglandular manifestations. However, no significant differences were observed in terms of ANA positivity, ANA titers, or ENA positivity. Regression analysis indicated that age and FS were linked to systemic involvement. Conclusion: This study highlights the importance of FS as a predictive indicator for extraglandular manifestations in SS. Advanced age was found to be associated with an increased likelihood of extraglandular involvement. Assessing FS and age can aid in predicting extraglandular manifestations.